Well-posedness and global attractors for a non-isothermal viscous relaxationof nonlocal Cahn-Hilliard equations - Joseph L. Shomberg (AIMS Mathematics, 2016)
We investigate a non-isothermal viscous relaxation of some nonlocal Cahn-Hilliard equations. This perturbation problem generates a family of solution operators exhibiting dissipation and conservation. The solution operators admit a family of compact global attractors that are bounded in a more regular phase-space